Effects of elevated temperature on osmoregulation and stress responses in Atlantic salmon Salmo salar smolts in fresh water and seawater. Issue 3 (26th September 2018) - Vargas‐Chacoff, Luis; Regish, Amy M.; Weinstock, Andrew; McCormick, Stephen D.
Abstract : Smolting in Atlantic salmon Salmo salar is a critical life‐history stage that is preparatory for downstream migration and entry to seawater that is regulated by abiotic variables including photoperiod and temperature. The present study was undertaken to determine the interaction of temperature and salinity on salinity tolerance, gill osmoregulatory proteins and cellular and endocrine stress in S. salar smolts. Fish were exposed to rapid changes in temperature (from 14 to 17, 20 and 24°C) in fresh water (FW) and seawater (SW), with and without prior acclimation and sampled after 2 and 8 days. Fish exposed simultaneously to SW and 24°C experienced 100% mortality, whereas no mortality occurred in any of the other groups. The highest temperature also resulted in poor ion regulation in SW with or without prior SW acclimation, whereas no substantial effect was observed in FW. Gill Na + –K + ‐ATPase (NKA) activity increased in SW fish compared to FW fish and decreased with high temperature in both FW and SW. Gill Nkaα1a abundance was high in FW and Nkaα1b and Na + –K + ‐2Cl‐ cotransporter high in SW, but all three were lower at the highest temperature. Gill Hsp70 levels were elevated in FW and SW at the highest temperature and increased with increasing temperature 2 days following direct transfer to SW. Plasma cortisol levels were elevated in SW at the highest temperature. Our results indicate that there is an important interaction of salinity and elevated temperature on osmoregulatory performance and the cellular stress response in S. salar, with an apparent threshold for osmoregulatory failure in SW above 20°C.